THE RELEVANCE OF THE CRITICAL PARADIGM TOWARDS LEARNING DESIGN DEVELOPMENT RESEARCH BASED ON REALISTIC MATHEMATICS EDUCATION (Universitas PGRI Sumatera Barat, 2022)
The paradigm in educational research is divided into several paradigms, namely positivism, interpretive and critical. The critical paradigm sees the relationship between the observer and reality as something that cannot be separated. This flow emphasizes the concept of subjectivity in finding a science. This view rejects the positivist and interpretative views which state that reality is value-free. Because this school holds that reality cannot be separated from the subject of the researcher, the values adopted by the subject also influence the truth of that reality. Data analysis is used related to journals and documents, based on data obtained and literature studies. The results show that understanding the development of learning design is seen using a critical paradigm. The theory used here uses learning design theory based on the fact that it has been clearly discovered by Plomp. The author's question here is: What is relationship between research development design Realistic Mathematics Education with a critical paradigm? And what is the relationship between teori and practical in development research of Realistic Mathematics Education?